Primary cancer of the fallopian tube - Herrera Calmet, Abelardo (2015)
We made a brief reminder of the etiology, pathology, symptoms. diagnosis, prognosis and treatment of early cancer of the fallopian tube. It has presented a case of adenocarcinoma of the tube associated with uterine fibroids, in which symptoms were the most frequent of the entity and yet not made the clinical and surgical diagnosis, being a finding of the pathologist. We believe that the diagnosis of carcinoma of the tube, although it is difficult, it can be done if we consider that possibility in the sick, especially menopausal, presenting vaginal discharge, bleeding, abdominal pain and pelvic tumor. The study of vaginal discharge, by the Papanicolaou method we consider of value in screening for this cancer.